LAMA PERENDAMAN AIR KELAPA MUDA UNTUK PERTUMBUHAN TUNAS CABANG PULAI GADING (Alstonia scholaris (L.)R. BR.) - Astuti, Riya; Mardhiansyah, Muhammad; Darlis, Viny Volcherina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Alstonia scholaris  is one of the plants used for revegetation activities in mining land reclamation activities. Vegetative seed procurement is an alternative to get more seedlings, namely by using ivory stems to cut branches. The growth of branch buds can be stimulated using natural growth regulators, namely coconut water. The purpose of this study was to determine the effect of coconut water for the growth of ivory branch buds and find out the optimal soaking time for the growth of ivory branch buds. This research was conducted in September-October 2019 in the experimental gardens of the Faculty of Agriculture, Riau University. This study uses a completely randomized design method consisting of 4 treatments and 4 replications with each stem cuttings soaked at several times, are K0 (without soaking), K1 (2 hours soaking time), K2 (4 hours soaking time), K3 (6 hours soaking time). The results of this study showed significant results for the time of emergence of buds, the number of buds, buds length, buds wet weight and dry weight of the ivory branch. The optimal soaking time for the growth of ivory branches is K1 (soaking time 2 hours) with number of buds 1,70 pieces, buds length 0,58 cm and dry weight 0,06 gr.Keywords: coconut water, Alstonia scholaris, growth regulator.